Theoretical and methodological bases of building a digital infrastructure of BIM-based management of capital construction projects - Savina, A. G.; Malyavkina, L. I.; Savin, D. A. (Russian Journal of Economics and Law, 2023)
Objective: to systematize methodological foundations and to construct a conceptual model of information modeling technology as a basis for its full-ﬂedged implementation with a view of improving the efﬁciency of investment and construction activities.Methods: review of information sources on the strategy of digital transformation of the construction industry; study of the regulatory system and retrospective analysis of the evolution of information modeling technology; systematization of information on its maturity levels; comparative analysis of analytical reviews and reports of leading consulting companies.Results: the essence of various semantic aspects of technology at the stages of its evolutionary development is investigated, the actual representation of information modeling technology is identiﬁed, a conceptual model is developed, and the features of technology from the viewpoint of process, technological and effective approaches are highlighted. The structural elements of the information model are determined, the dynamic processes of formation and progressive transformation of its components are described. The assessment of the current level of technology maturity in the Russian construction industry is carried out based on the Bew–Richards model; the importance of its full integration into the life cycle management system of the capital construction project to improve the efﬁciency of each stage of the investment and construction project implementation is substantiated.Scientiﬁc novelty: a modern interpretation of information modeling technology is presented, a conceptual model is developed on the basis of an integrated approach and its key elements are identiﬁed.Practical signiﬁcance: the main provisions of the article and the developed conceptual model can be used by the subjects of the architectural and construction industry in developing a digital transformation strategy based on information modeling technology, in scientiﬁc research of theoretical and practical aspects of technology application, as well as in the educational process in the training of specialists in the construction industry.